Forestry Land Use Planning Using Remote Sensing, GIS and Rapid Rural Appraisal Techniques - Pant, D. N.; Than Naig, U. (Indian Forester, 2007)
This paper deals with forestry land use planning of Lachhiwala Forest Range, Dehra Dun Forest Division, Uttarakhand, India based on the changes within its forests and the people’s dependency on them. The methods consist of the preparation of forest type, density, land use change maps based on the visual interpretation of IRS-1C LISS III (1998) and Landsat TM data (1986) and household sample data using Rapid Rural Appraisal technique. The spatial and non spatial database were generated using PC based Arc/View 3.2a. A digital elevation model and subsequent slope map, buffer from stream/nala, forest type and density, adverse changes within forest area and the location of picnic spot were taken as parameters for developing a matrix and subsequent modeling for the creation of a final map showing the potential forestry land uses. The study reveals about 23% negative change due to heavy biotic pressure inside the forest in the past. The present estimates with respect to the amount of full and partial dependency of people on the forest highlight the continuity of its degradation. It has been planned to classify the existing forests of study area into different forestry land uses for sustainable forest management and reducing the dependency of people on them through Joint Forest Management (JFM) and agro-forestry schemes.